2015
DOI: 10.1042/cs20140530
|View full text |Cite|
|
Sign up to set email alerts
|

Non-small-cell lung cancer and miRNAs: novel biomarkers and promising tools for treatment

Abstract: Lung cancer is the leading cause of cancer-related death worldwide, with approximately 80-85% of cases being non-small-cell lung cancer (NSCLC). The miRNAs are small non-coding RNAs that regulate gene expression at a post-transcriptional level by either degradation or inhibition of the translation of target genes. Evidence is mounting that miRNAs exert pivotal effects in the development and progression of human malignancies, including NSCLC. A better understanding of the role that miRNAs play in the disease wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 168 publications
1
59
0
Order By: Relevance
“…PTEN expression is decreased in patients with NSCLC, and its deficiency is linked to cancer development and progression [32,33]. Growing evidence has shown that PTEN inhibited tumor cell growth and invasion by blocking the PI3K/Akt pathway [27] since it can negatively regulate the activity of Akt pathway by dephosphorylating PIP3 at the 3-phosphate site [24]. In this present study, we further confirmed that PTEN is a direct target of miR-92a in NSCLC by luciferase reporter assays, qRT-PCR, and western blotting assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTEN expression is decreased in patients with NSCLC, and its deficiency is linked to cancer development and progression [32,33]. Growing evidence has shown that PTEN inhibited tumor cell growth and invasion by blocking the PI3K/Akt pathway [27] since it can negatively regulate the activity of Akt pathway by dephosphorylating PIP3 at the 3-phosphate site [24]. In this present study, we further confirmed that PTEN is a direct target of miR-92a in NSCLC by luciferase reporter assays, qRT-PCR, and western blotting assay.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence has suggested that aberrant expression of miRNAs plays important roles in NSCLC occurrence and development [14,15]. Therefore, identification of NSCLC-specific miRNAs and their targets is critical for understanding their roles in NSCLC tumorigenesis, which may contribute to find out diagnosis marker and novel therapeutic targets for NSCLC [24]. In the current study, we observed that miR-92a was upregulated in NSCLC compared with adjacent non-cancerous tissues, and its expression was significantly correlated with clinicopathological features, including lymph node metastasis (P < 0.01), tumor size (P<0.01), and TNM stage (P<0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are involved in the pathogenesis of lung diseases, including lung cancer, cystic fibrosis, chronic obstructive pulmonary disease, asthma and idiopathic pulmonary fibrosis (12). miRNAs contribute to the development of novel diagnostic biomarkers and personalized therapeutic tools in NSCLC (13). miR-145 is silenced by DNA methylation and acts as a prognostic biomarker in NSCLC (14).…”
Section: Introductionmentioning
confidence: 99%
“…It has become increasingly evident that different miRNAs can play either oncogenic or tumor-suppressive roles in a wide variety of pathways, depending on the target genes or the cellular context (6,7). miR-200c is a member of the miR-200 family, which consists of five members (miR-200a, miR-200b and miR-429 comprise cluster 1, which is located on chromosome 1p36; and miR-200c and miR-141 comprise cluster 2, which is located on chromosome 12p13) (8).…”
Section: Introductionmentioning
confidence: 99%